2010
DOI: 10.1111/j.1540-8175.2010.01235.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Left Ventricular Volumes and Function by Real Time Three‐Dimensional Echocardiography in a Pediatric Population: A TomTec versus QLAB Comparison

Abstract: 3D LV volume quantification is feasible either by using manual or automated reconstruction software in a normal pediatric population. LV Measurements are well correlated. Differences in volume reconstruction algorithms provide specific software performance characteristics. TomTec is a more feasible method but requires a longer analysis time. Further studies are needed to validate the accuracy of the method to calculate enlarged LV volumes in patients with congenital heart diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
29
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 35 publications
10
29
1
Order By: Relevance
“…They can be assessed by tissue deformation imaging using speckle tracking, CMR tagging [22] as well as by three dimensional techniques to measure changes in blood pool volumes throughout the cardiac cycle. With the introduction of model-based analysis algorithms motional details such as parametric maps for dynamic visualization of contraction time or assessment of mechanical dyssynchrony are now accessible [7,16,23,24] which are easy and quick to apply but accuracy and reliability of functional LV parameters still have to be investigated further. It was the aim of this study to consolidate the promising volumetric results in healthy pediatric individuals assessed by RT3DE in a former study [5] by examining asymmetrically shaped gel phantoms and a patient group with predominantly dilated left ventricles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They can be assessed by tissue deformation imaging using speckle tracking, CMR tagging [22] as well as by three dimensional techniques to measure changes in blood pool volumes throughout the cardiac cycle. With the introduction of model-based analysis algorithms motional details such as parametric maps for dynamic visualization of contraction time or assessment of mechanical dyssynchrony are now accessible [7,16,23,24] which are easy and quick to apply but accuracy and reliability of functional LV parameters still have to be investigated further. It was the aim of this study to consolidate the promising volumetric results in healthy pediatric individuals assessed by RT3DE in a former study [5] by examining asymmetrically shaped gel phantoms and a patient group with predominantly dilated left ventricles.…”
Section: Discussionmentioning
confidence: 99%
“…Especially RT3DE tools provide a timesaving workflow generating volumes as well as volume-time curves in order to assess dyssynchrony and regional function. They use model-dependent contour tracking algorithms or speckle-tracking based approaches [7,[14][15][16] . In summary they provide reliable and reproducible data about LV-EF with mild or moderate underestimation of volumes.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous validation studies have demonstrated that 3DE compares favorably with other independent reference standards such as CMR and is superior for assessing left ventricular volumes, mass, and ejection fractions in adults. [49][50][51][52][53][54][55] We have also found that RE3VD is more accurate and reproducible than M-mode and the 2D Simpson's biplane method and is as efficient as 2DE in children. 32 The validation studies in the pediatric population are listed in Table I.…”
Section: Assessment Of Volumes and Function Of LV Rv And Svmentioning
confidence: 94%
“…Hascoet et al have compared QLAB 6.0[Phillips] which is a semi-automated system with TomTec 4D LV which is primary manual tracking with semi-automated border detection. They found that 3D volume assessment was feasible using both systems with good correlation of LV volume measurements [8]. When performing 3D volumetric assessment, particularly with semi automated border detection, stitching artefacts will impair the ability of the software to track the image.…”
Section: Three Dimensional Echocardiographymentioning
confidence: 99%